Student Learning Motivation in Music Technology Learning in Class XII Music SMK N 7 Padang - Winda Oktavia; Irdhan Epria Darma Putra (Universitas Negeri Padang, 2023)
This study aims to discover and describe how the implementation of track era getting to know in magnificence XII tune SMK N 7 Padang. This kind of studies is qualitative using descriptive strategies. Observations and interviews, researchers determined that there are numerous extrinsic factors that are not discovered inside the teaching and mastering method, together with the absence of support from instructors for all college students, the absence of strict rules all through PBM and the absence of appreciation from instructors associated with pupil fulfillment, however there are also other elements along with economics intrinsic and extrinsic motivation is the inducement wanted by means of every toddler, because every motivation has a dependence between motivation from within and motivation from the surroundings or from out of doors, the lifestyles of intrinsic motivation because of encouragement from outdoor and the surroundings (extrinsic).